2012
DOI: 10.1007/s12264-012-1251-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of multi-electrode array recordings in studies of network synaptic plasticity in both time and space

Abstract: Simultaneous multisite recording using multi-electrode arrays (MEAs) in cultured and acutely-dissociated brain slices and other tissues is an emerging technique in the field of network electrophysiology. Over the past 40 years, great efforts have been made by both scientists and commercial concerns, to advance this technique. The MEA technique has been widely applied to many regions of the brain, retina, heart and smooth muscle in various studies at the network level.The present review starts from the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 49 publications
1
28
0
1
Order By: Relevance
“…In in-vitro networks, multielectrode arrays (MEAs) can be used to stimulate many neurons at the same time, as well as to measure their activity [46]. For our purposes, an MEA could be used to trigger plasticity, forming a strongly interconnected cell assembly.…”
Section: Testing Our Predictions In Experimentsmentioning
confidence: 99%
“…In in-vitro networks, multielectrode arrays (MEAs) can be used to stimulate many neurons at the same time, as well as to measure their activity [46]. For our purposes, an MEA could be used to trigger plasticity, forming a strongly interconnected cell assembly.…”
Section: Testing Our Predictions In Experimentsmentioning
confidence: 99%
“…In the field of modern in vitro neuroscience, a mainstay methodology to study network-level electrophysiological properties of neuronal cell ensembles relies on non invasive substrateintegrated matrices of microelectrodes (i.e., Microelectrode Arrays or MEAs) functioning as interfaces between neuronal cultures and electronic readout systems (Johnstone et al, 2010;Nam and Wheeler, 2011;Obien et al, 2015). Nowadays, MEAs are routinely deployed in a bulk of applications, spanning studies about network dynamics (Biffi et al, 2013;Li et al, 2007;Wagenaar et al, 2006), neuronal plasticity (Liu et al, 2012), and drug screenings (Johnstone et al, 2010;Robinette et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, this is consistent with many other studies in mouse models of DS and GEFS+ that show unaltered excitability of pyramidal neurons (Cheah et The ultimate goal of our study is to develop mechanism-based drug therapies using our mouse model that recapitulates seizure phenotypes in human patients. The micro-electrode array (MEA) system is emerging as a powerful tool to examine long term neural network activity in rodent brain slices or neuronal cultures in response to pharmacological drugs (Jensen, 2019;Liu et al, 2012;McConnell et al, 2012;Valdivia et al, 2014). Previous studies have shown that the MEA can be utilized for recording spontaneous neuronal activity from acute hippocampal cultures derived from R1648H mouse (Hedrich et al, 2014) and screen anti-convulsant drugs in rat brain slices (Fan et al, 2019).…”
Section: Comparison With the Existing Models Of K1270t Mutationmentioning
confidence: 99%